AlCrN/Cr3C2–NiCr duplex coating towards high load-bearing and dry sliding antiwear applications. Issue 13 (1st July 2022) - Zheng, Wenwen; He, Dongqing; Li, Wensheng; Shang, Lunlin; Song, Qiang; Zhang, Guangan; Zhai, Haimin; Cheng, Bo
Abstract: In this study, experimental analysis and finite element modeling (FEM) were employed to investigate the microstructure and mechanical properties of duplex coatings composed of a Cr3 C2 –NiCr interlayer and a top AlCrN film in comparison with these of a single AlCrN film. Results showed a significant improvement in the adhesive strength, load-bearing capacity, H/E, and H 3 /E 2 ratios, and hardness of the AlCrN/Cr3 C2 –NiCr duplex coatings compared to the single AlCrN film, especially the wear resistance that increased by nearly eight times under heavy loads. Moreover, FEM analysis revealed that the duplex design reduced the stress concentration area on the surface of AlCrN film and kept it far away from the contact interface during load-bearing.